Effect of frozen duration on the quality of cow liver - Rabbi, MF; Kibria, SE; Rahman, MM; Hashem, MA; Khan, M (Meat Research, 2024)
The experiment was conducted to find out the effect of frozen duration (-20°C) on the quality of raw cow liver. For this purpose, raw cow liver samples were divided into three treatment groups. They were treated as 0 days, 60 days, and 120 days as T1, T2, and T3 respectively. Sensory parameters (color, odor, juiciness and tenderness), proximate analysis (DM, CP, EE Ash), pH value, cooking loss, water holding capacity, TBARS value and microbiological examination were determined in order to evaluate the quality of raw cow liver at different frozen duration. Color, odor, juiciness, and tenderness were decreased among different frozen duration significantly (p<0.05). Dry matter content increased (p<0.05) with the increase of storage days. CP and EE content decreased (p<0.05) with the increase of storage days. As well as with the advancement of days, ash content were increased significantly (p<0.05). pH values were decreased with the increase of storage days. The cooking loss (%) were increased (p<0.05) with the increase of storage days. Water holding capacity were decreased (p<0.05) with the increase of storage days. Thiobarbituric acid values were increased (p<0.05) with the increase of storage days. TVC (log CFU/g), TCC (log CFU/g), and TYMC (log CFU/g) were increased (p<0.05) with the increase of storage days comparison to 0 days. In conclusion, from this study on sensory evaluation, nutritional content, physicochemical properties, biochemical analysis and microbial assessments, it has been found that up to 120 days is safe for human consumption.